A Data Mining Study for Analysis of Acupoint Selection and Combinations in Acupuncture Treatment of Carpal Tunnel Syndrome [Response to Letter] - He Y (Journal of Pain Research)
Yujun He Department of Traditional Chinese Medicine, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Taizhou City, People’s Republic of ChinaCorrespondence: Yujun He, Department of Traditional Chinese Medicine, Taizhou Hospital of Zhejiang Province, Taizhou City, People’s Republic of China, Email 422346582@qq.com